Chemical characterization, hydrolysis and bioethanol production from municipal solid waste - Oliveira, Fabíola Ribeiro de [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Food waste is increasing in the world and this residue when inappropriately disposed, cause serious problems in the environment, due to its toxicity for soil and water. Then, new technologies for the use of municipal solid waste (MSW) can decrease its damage to nature and expenses for society, besides open up the opportunity to obtain value-added products.There is also a strong interest in the development of fuels from renewable sources, aiming at lower environmental impacts than the widely used fossil fuels. In view of this, biomass from MSW is known for its great potential as a source for biofuels and biomolecules production. Therefore, the present work aimed to produce ethanol from the organic portion of the MSW. The proposed technology conforms to the concept of biorefinery, and it consisted in the enzymatic hydrolysis using glucoamylases produced by Rhizopus oligosporus in solid-state cultivation, through technology patented by UNESP (BR 102014031591-8 A2), which showed a conversion capacity of starch to reducing sugars (RS) of 67.38%, followed by alcoholic fermentation by Saccharomyces cerevisiae, producing 0.25 g of ethanol per gram of reducing sugar offered. Therefore, it was found that use of this lower cost source of enzyme results in good hydrolysis yielding, and consequently, considerable bioethanol production from MSW.

O desperdício de alimentos está aumentando no mundo e esse resíduo quando descartado de forma inadequada, causa sérios problemas ao meio ambiente, devido a sua toxicidade para o solo e a água. Assim, novas tecnologias de aproveitamento de resíduos sólidos urbanos (RSU) podem diminuir seus danos à natureza e gastos para a sociedade, além de abrir a oportunidade de obtenção de produtos de valor agregado. Existe ainda, um grande interesse no desenvolvimento de combustíveis provindos de fontes renováveis, visando impactos ambientais menores do que os combustíveis fósseis amplamente utilizados. Diante disso, a biomassa de RSU é conhecida por seu grande potencial como fonte para produção de biocombustíveis e biomoléculas. Portanto, o presente trabalho teve como objetivo produzir etanol a partir da porção orgânica do RSU. A tecnologia proposta está em conformidade com o conceito de biorrefinaria, e consistiu na hidrólise enzimática utilizando glucoamilases produzidas por Rhizopus oligosporus em cultivo em estado sólido, por meio de tecnologia patenteada pela UNESP (BR 102014031591-8 A2), que mostrou capacidade de conversão de amido em açúcares redutores (AR) de 67,38%, seguido de fermentação alcoólica por Saccharomyces cerevisiae, produzindo 0,25 g de etanol por grama de açúcar redutor ofertado. Portanto, verificou-se que o uso desta fonte de enzima de menor custo resulta em um bom rendimento de hidrólise e, consequentemente, uma produção considerável de bioetanol a partir de RSU.
Caracterização química, hidrólise e produção de bioetanol a partir de resíduos sólidos urbanos
Keywords: Biomassa; Biorrefinaria; Fermentação; Açúcares redutores; Hidrólise enzimática